2016
DOI: 10.1515/med-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission through icotinib treatment in Non-small cell lung cancer epidermal growth factor receptor mutation patient with brain metastasis: A case report

Abstract: AbstractBrain metastasis (BM) has been universally recognized as a poor prognostic factor in non-small cell lung cancer (NSCLC). Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have shown efficacy in treating BM with an EGFR mutation. This paper reports a case of BM patient with EGFR-mutated NSCLC. According to the findings, a complete remission (CR) of the BM was achieved by icotinib treatment without conducting a radiotherapy, which was followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Among the 24 publications, one publication [ 19 ] has no data for DCRs; DCRs were 100% in EGFR mutant patients and EGFR wild type patients in two publications [ 12 , 20 ]. After excluding these 3 publications, 21 publications having 1127 patients including 750 EGFR mutant patients and 377 EGFR wild type patients were enrolled in meta-analysis for DCRs.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 24 publications, one publication [ 19 ] has no data for DCRs; DCRs were 100% in EGFR mutant patients and EGFR wild type patients in two publications [ 12 , 20 ]. After excluding these 3 publications, 21 publications having 1127 patients including 750 EGFR mutant patients and 377 EGFR wild type patients were enrolled in meta-analysis for DCRs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 19-Del and 21-L858R mutations are associated with distinguishing clinical characteristics [11]. A previous study has revealed that the efficacy of EGFR-TKIs are associated with the EGFR mutations, especially exon 19 and exon 21 that are sensitive to targeted drug therapies [12][13][14][15]. Moreover, patients with 19-Del showed better clinical outcomes than those with 21-L858R when treated with EGFR-TKIs [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%